Study and proposal of iconography suitable for use in inclusive multimodal applications of electric power concessionaires (Revista Brasileira de Contabilidade e Gestão, 2016)
Currently, it is estimated that 15% of the world population have some kind of physical or sensory disability and over 20% have low levels of literacy. Nowadays, the evolution of electronic devices grows rapidly with the increase of computing power and the creation of new devices. People with disabilities, however, often still face many barriers when interacting with these devices, which let them out of this digital society. In this sense, many initiatives have been taken to solve or mitigate this problem. In this sense, it was proposed by *** a project that is expected to create an agency with accessible customer service in order to be used by anyone. The aim of this project is to provide a physical environment in which everyone can order electrical services with little or no help from human facilitators through multimodal devices and interfaces. This led us to studies involving best practices of interaction design in order to effectively meet the target audience. This paper describes the iconographic solution designed to make multimodal interfaces more effective and inclusive. This efficacy was measured compared to a set of icons currently being used in a Web system of this company.
Keywords: iconography; icons; intelligibility; accessibility; eletrical energy